Productivity of intermediate wheatgrass responds more to local soil and climate factors than fertility treatments in the first establishment year - Cassani, M. Tomás; Gutknecht, Jessica L.; Basche, Andrea; Brunsell, Nathaniel A.; Crews, Timothy E.; Culman, Steven; Deiss, Leonardo; Laboski, Carrie A. M.; Picasso, Valentín; Pinto, Priscila; Bianchin Rebesquini, Roberta; Tautges, Nicole E.; et al. (Frontiers in Agronomy, 2025)
The intensive cultivation practices of annual cereal crops have been causing unprecedented degradation of natural resources. Perennial crops such as intermediate wheatgrass (IWG) could provide numerous benefits to address these issues, but there is still little comprehensive information about the establishment, fertilization needs, or range of IWG productivity on a regional basis in the first production year, which can be the highest over the lifespan of IWG’s grain production. The objective of this study was to evaluate how IWG establishment and first-year grain and forage yields varied across soil types, climate conditions, and in response ten fertilization treatments at six locations in the Midwestern USA. The 10 treatments included N fertilizer application at 5 rates; N application with or without P or K; varied timing of N application, and varied N fertilizer source. We found that fertilization influenced summer and fall forage yields but not grain yields. We also found that grain and forage yields varied greatly between locations, ranging from 556–1343 kg ha-1 for grain yields, 3732–8930 kg ha-1 for summer forage, and 927–3561 kg ha-1 for fall forage yields. Using a multiple linear regression approach, we found that a combination of local edaphic soil and climate factors explained 74%, 92%, and 69% of variance in grain, summer forage, and fall forage yields, respectively. Anomalies in expected and actual yields across locations led us to identify potential critical periods for IWG grain and forage production. We found accumulated precipitation in the 60 days before anthesis explained the most variance in grain and summer forage yields while the accumulated precipitation from May through October explained the most variance in fall forage yields. These findings are a first step toward identifying the regional expectations for IWG yields and could inform grower management and decisions regarding grain and forage harvest.